Estudo de preconceito social em relação à periferia por meio do IRAP - Souza, Washington Santos de (2020)
Behavior analysis is a science that is concerned with social issues and how such cultural practices are related to behaviors. In order to assess those relations, tools for measuring implicit attitudes have been developed, such as the Implicit Relational Assessment Procedure (IRAP). This study aimed to assess prejudice related to the periphery of the city of São Paulo, Brazil, with the following objectives: (a) evaluating the existence of biases in relation to images of peripheral neighborhoods of São Paulo and social prejudice among the participants; (b) if so, if those biases would be lower in residents of peripheral neighborhoods; and (c) verifying whether variables from a personal history of urban violence could be related to biases. There were 26 participants, aged between 18-57 years, which were split into four groups: (a) residents of peripheral neighborhoods who had experienced episodes of violence; (b) residents of peripheral neighborhoods who had not experienced episodes of violence; (c) residents of upscale neighborhoods who had experienced episodes of violence; and (d) residents of upscale neighborhoods who had not experienced episodes of violence. According to the results, no group showed biases related to the periphery, and participants living in upscale neighborhoods rated the images of peripheral neighborhoods more positively than those living in peripheral neighborhoods. It was not possible to verify whether variables related to urban violence influenced biases